SME users in Industry 4.0 Study of the Metalworking Industry in Argentina - Alicia Mon; Horacio Del Giorgio; Geraldina Roark; Carolina Saavedra Sueldo; Ivo Perez Colo; Mariano De Paula (CLEI Electronic Journal)
In the era of Industry 4.0, the success of the adoption of advanced technologies depends on how they are assimilated and incorporated into current production systems. This work focuses on analyzing the state of technological adoption in Small and Medium Enterprises (SMEs) in the metalworking sector in Argentina, analyzing the ICT products implemented in each of the functional areas of the company that maintain interaction with the people who operate them and identifying the knowledge and capabilities of real users for each functional area. For this purpose, an expanded InTICs®methodology was used to measure the degree of technological maturity of a productive company. The obtained results show that most of the companies surveyed present a medium level of technological maturity, with variations depending on their size. Microenterprises tend to register a basic level of maturity, while medium and large companies show greater adoption of advanced technologies. These results offer a detailed vision of the integration of Industry 4.0 technologies in Argentine metalworking SMEs, providing valuable information to identify users and the levels of interaction between people and the technologies they operate, as well as to analyze the required human capabilities and training strategies to promote digital transformation in this sector.